Análise eletromiográfica da marcha de idosos saudáveis e com Doença de Parkinson durante a simulação de travessia de rua - Sousa, Lucas Resende (2017)
Cross the street is a daily action that requires planning and cognitive demand. Changes in the gait of healthy elderly subjects and with Parkinson's disease (PD) can make the street crossing a risk situation and cause accidents. The objective of this study was to analyze the crossing time and the level of activation of the vastus lateralis (VL), bíceps femoralis (BF), anterior tibialis (TA) and lateral gastrocnemius (GL) of 21 healthy elderly subjects (GIS) and 19 with PD (GIDP) during 3 street crossing situations: gait with comfortable speed (I), gait during simulated street crossing (II), and gait during simulated street crossing with reduced time (III). In GIS, the muscular activation of VL and BF was higher in condition II than in condition I, higher in condition III than in condition I and higher in condition III than in condition II; Of TA and GA was not different between conditions II and I, was higher in condition III than in condition I and higher in condition III than in condition II. In GIDP, the muscular activation level of all muscles was higher in condition II than in condition I, higher in condition III than in condition I and higher in condition III than in condition II. According to the difficulty of the task, both groups reduced the crossing time. There was an effect of gait condition on crossing time and muscle activity in the groups, and GIDP is more influenced by increase of gait velocity in TA and GL muscles compared to GIS.